Prioritising the investigation of organised crime - Sullivan, Trudy (Policing and society, 2020)
Organised crime is becoming increasingly sophisticated and pervasive. Responding effectively to the dynamic and multifaceted nature of organised criminal activity is challenging. Law enforcement agencies need to find new and innovative ways to meet the demands of an ever-increasing and complex workload. Targeting resources is essential if the associated cost of organised crime is to be contained. This paper outlines a novel approach for ranking offenders specifically within the field of organised crime, in terms of investigative priority. Thirteen key people involved in the investigation of organised crime in New Zealand were brought together for a one-day workshop. Prior to attending the workshop participants were asked to rank 12 hypothetical offender profiles in terms of investigative priority. The rankings were used to stimulate discussion on the major issues relating to organised crime. As a result, six criteria were identified, and a discrete choice experiment was completed by consensus to determine the relative importance of the criteria. Community harm was considered the most important criterion (0.26), followed by corruption or infiltration (0.17), geographical influence (0.16), convertible assets (0.15), capability (0.14) and criminal influence (0.12). Fifty front-line investigators subsequently completed the experiment online, and the relative weights were found to be similar to those from the workshop. To assess the practicability of the weights, 10 known high-risk offenders were categorised and ranked using the weighted criteria from the workshop. Senior staff involved in the investigation of these offenders agreed that the resulting ranking of offenders aligned with their personal judgement.